Home-Based Long-Term Physical Endurance and Inspiratory Muscle Training for Children and Adults With Fontan Circulation—Initial Results From a Prospective Study - Dirks, Stefan; Kramer, Peter; Schleiger, Anastasia; Speck, Hans-Martin; Wolfarth, Bernd; Thouet, Thomas; Berger, Felix; Sallmon, Hannes; Ovroutski, Stanislav (Frontiers in Cardiovascular Medicine, 2022)
Background Patients with congenital heart disease (CHD)—including those after Fontan operation—are encouraged to be physically active. Aim To prospectively determine the effects of an individually adapted, home-based cycle ergometer endurance training in combination with inspiratory muscle training (IMT) in pediatric and adult Fontan patients. We, herein, report the results of the initial 10-months follow-up (phase 1). Methods 18 patients (median age 16.5 years; range 10-43 years) completed baseline check-ups, and 4 and 10 months follow-up visits, which each included cardiopulmonary exercise testing (CPET), bodyplethysmography (including measurement of respiratory muscle strength), and a quality of life questionnaire (PedsQL™). The training program consisted of a home-based cycle ergometer endurance training on a “Magbike® AM-5i/3i” (DKN Technology®, Clermont-Ferrand, France) and IMT with a handheld “POWERbreathe® Medic plus” device. Patients performed 90 min of endurance training per week in addition to IMT (30 breaths per day, 6-7 times per week). After the first 4 months, patients underwent additional interval training. Results After 10 months of training, we observed significant increases in maximum relative workload (W/kg, p = 0.003) and in maximum inspiratory (MIP, p = 0.002) and expiratory (MEP, p = 0.008) pressures. Peak VO2 values did not increase significantly as compared to baseline (p = 0.12) in the entire cohort (n = 18), but reached statistical significance in a subgroup analysis of teenage/adult patients (n = 14; p = 0.03). Patients' subjective quality of life did not show any significant changes after 10 months of training. Discussion In Fontan patients, an individually adapted home-based training is safe and associated with improvements in some CPET variables. However, these improvements did not translate into an improved QoL after 10 months. With an unclear, but most likely negative, impact of the COVID-19 pandemic, improvements in QoL may become evident during further follow-up (phase 2 of the study).